2021
DOI: 10.1029/2020wr028827
|View full text |Cite
|
Sign up to set email alerts
|

Soil Moisture Responses to Rainfall: Implications for Runoff Generation

Abstract: Soil moisture is a key control on runoff generation and biogeochemical processes on hillslopes. Precipitation events can evoke different soil moisture responses with depth through the soil profile, and responses can differ among landscape positions along a hillslope. We sought to elucidate the nature of these responses by estimating changes in water content, response time between peak precipitation and peak soil moisture, and wetting front velocities for 43 storms at 45 locations on three adjacent hillslopes w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
40
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 63 publications
(55 citation statements)
references
References 97 publications
4
40
0
Order By: Relevance
“…(2009) found similar spatial heterogeneity following precipitation events in sandy volcanic soils, attributing much of the variability across space to preferential flow pathways. Similarly, a large analysis of storm events across watersheds in the southern Appalachian mountains also found that soil moisture responses varied widely depending on hillslope properties, storm characteristics, and antecedent conditions (Singh et al., 2021).…”
Section: Discussionmentioning
confidence: 97%
“…(2009) found similar spatial heterogeneity following precipitation events in sandy volcanic soils, attributing much of the variability across space to preferential flow pathways. Similarly, a large analysis of storm events across watersheds in the southern Appalachian mountains also found that soil moisture responses varied widely depending on hillslope properties, storm characteristics, and antecedent conditions (Singh et al., 2021).…”
Section: Discussionmentioning
confidence: 97%
“…We calculated three different rainfall event response metrics for each soil moisture, perched water tables at the soil-epikarst interface, and runoff flow on a storm-by-storm basis (Figure 3). We defined a minimum threshold for soil moisture response as a generated change of 0.01 cm 3 cm À3 in 30 min (Singh et al, 2021). The peak value time was defined as the time difference between the time of maximum rainfall intensity at 30 min intervals and the time of peak soil moisture, water table, and runoff flow (Singh et al, 2021).…”
Section: Response Metricsmentioning
confidence: 99%
“…We defined a minimum threshold for soil moisture response as a generated change of 0.01 cm 3 cm À3 in 30 min (Singh et al, 2021). The peak value time was defined as the time difference between the time of maximum rainfall intensity at 30 min intervals and the time of peak soil moisture, water table, and runoff flow (Singh et al, 2021). Residual time was defined as the maximum value time minus the change in values in the first 30 min.…”
Section: Response Metricsmentioning
confidence: 99%
“…In Australia, the amount of rainfall and the timing of the beginning of the wet season vary from regions hence affects the time of year when soil moisture peaks in different regions. When the wet season arrives, SSM would rise significantly in a short period of time (Li et al., 2015; Singh et al., 2021). By contrast, the growth of vegetation leaves is a relatively slower process, so there might be a time lag between the two. Regarding the impact on SSM from plants.…”
Section: Discussionmentioning
confidence: 99%
“…For example, woody vegetation covers large areas in the southeast and eastern regions, the northeast and northern areas are mainly covered with savannas and grasslands, and the southwest areas are covered with shrublands and forests. The time lag might vary from different regions of Australia. Rainfall is one of the most important sources of SSM in some regions (Singh et al., 2021), and SSM shares an obvious and strong physical connection with rainfall (Koster Randal et al., 2004; Taylor, 2001). On the one hand, on a regional scale, antecedent SSM has a significant impact on the rainfall‐triggering mechanism.…”
Section: Discussionmentioning
confidence: 99%